Cover Feature: Pathways to Triplet or Singlet Oxygen during the Dissociation of Alkali Metal Superoxides: Insights by Multireference Calculations of Molecular Model Systems (Chem. Eur. J. 11/2020). Issue 11 (16th December 2019) - Zaichenko, Aleksandr; Schröder, Daniel; Janek, Jürgen; Mollenhauer, Doreen
Abstract : The triplet and singlet oxygen generation during the dissociation of alkali superoxides has been investigated by multireference calculations. The understanding of the detailed reaction mechanism makes it possible to design strategies to avoid the formation of unwanted singlet oxygen and the related degradation of materials in lithium/oxygen batteries. Qualitatively similar reaction mechanisms have been obtained for the analogous alkali metals sodium and potassium and their superoxide species. More information can be found in the Full Paper by D. Mollenhauer et al. on page 2395 .